2005
DOI: 10.1002/jpln.200420434
|View full text |Cite
|
Sign up to set email alerts
|

Root morphology of Thlaspi goesingense Hálácsy grown on a serpentine soil

Abstract: The contribution of root morphology to enhanced uptake of heavy metals by hyperaccumulating plants is not well understood. The objective of this study was to describe root-morphological characteristics of the natural nickel (Ni) hyperaccumulator Thlaspi goesingense Hµlµcsy. Plant samples were collected from a serpentine site near Redlschlag (East Austria), characterized by large soil Ni concentrations. Roots were evaluated for mass, length, surface area, diameter, and related ratios using an image-analysis app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Therefore, values given for T. caerulescens by Sterckeman et al (2004) may have largely underestimated the true root length. Similar characteristics of fine roots and root hairs as observed in the present study have recently been reported also for the metal hyperaccumulator Thlaspi goesingense (Himmelbauer et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, values given for T. caerulescens by Sterckeman et al (2004) may have largely underestimated the true root length. Similar characteristics of fine roots and root hairs as observed in the present study have recently been reported also for the metal hyperaccumulator Thlaspi goesingense (Himmelbauer et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Shoots were cut at the soil surface and were separated. Roots were excavated to a depth of 30 cm and then completely immersed in a water‐filled container and washed with tap water until free of soil (Himmelbauer et al, 2005). Nodules on the root system were picked off and counted.…”
Section: Methodsmentioning
confidence: 99%
“…Rather than conducting comparisons between species, studies have focused on root length, depth, and surface area within a single species. Several hyperaccumulators have been described with small, shallow (<0.5 m) root systems and a high proportion of fine roots that contribute to trace element accumulation (Keller et al 2003;Himmelbauer et al 2005). Although these reports featured shallowrooted plants, deep-rooted (2 m) herbaceous species such as Biscutella laevigata (Cd-hyperaccumulator) exist (Kutschera and Lichtenegger 1992), and roots of many hyperaccumulator tree species remain unexamined but could be large and deep.…”
Section: Root Physical Characteristicsmentioning
confidence: 96%